Examining Noncardiac Surgical Procedures in Patients on Extracorporeal Membrane Oxygenation. Issue 5 (September 2015) - Taghavi, Sharven; Jayarajan, Senthil N.; Mangi, Abeel A.; Hollenbach, Kathryn; Dauer, Elizabeth; Sjoholm, Lars O.; Pathak, Abhijit; Santora, Thomas A.; Goldberg, Amy J.; Rappold, Joseph F.
Abstract : As extracorporeal membrane oxygenation (ECMO) is increasingly used for patients with cardiac and/or pulmonary failure, the need for noncardiac surgical procedures (NCSPs) in these patients will continue to increase. This study examined the NCSP required in patients supported with ECMO and determined which variables affect outcomes. The National Inpatient Sample Database was examined for patients supported with ECMO from 2007 to 2010. There were 563 patients requiring ECMO during the study period. Of these, 269 (47.8%) required 380 NCSPs. There were 149 (39.2%) general surgical procedures, with abdominal exploration/bowel resection (18.2%) being most common. Vascular (29.5%) and thoracic procedures (23.4%) were also common. Patients requiring NCSP had longer median length of stay (15.5 vs. 9.2 days, p = 0.001), more wound infections (7.4% vs. 3.7%, p = 0.02), and more bleeding complications (27.9% vs. 17.3%, p = 0.01). The incidences of other complications and inpatient mortality (54.3% vs. 58.2%, p = 0.54) were similar. On logistic regression, the requirement of NCSPs was not associated with mortality (odds ratio [OR]: 0.91, 95% confidence interval [CI]: 0.68–1.23, p = 0.17). However, requirement of blood transfusion was associated with mortality (OR: 1.70, 95% CI: 1.06–2.74, p = 0.03). Although NCSPs in patients supported with ECMO does not increase mortality, it results in increased morbidity and longer hospital stay.